Staelia culcita (Rubiaceae), a new species from Minas Gerais, Brazil - Salas, Roberto Manuel (2011)
Background – The genus Staelia (Rubiaceae) remains imperfectly known. As part of the revision of the genus by the first author, a new species is here described and illustrated. Methods – Normal practices of herbarium taxonomy were used to study all the herbarium material available. Key results – Staelia culcita R.M.Salas y E.L.Cabral, a new species from Brazil, is described and illustrated. The new taxon is apparently endemic to the Espinhaço mountain range, Minas Gerais, in campos rupestres montane savannas. It resembles Staelia hatschbachii in its small habit but differs in the opposite and narrowly elliptic leaves with ciliate base (vs. whorled linear leaves with glabrous base), the corolla lobes that are distinctly shorter than the corolla tube (vs. corolla lobes equal or longer than corolla tube), the calyx lobes that are much shorter than the corolla tube (vs. calyx lobes longer than corolla tube) and the reticulo-papillate seed coat surface (vs. reticulo-foveate seed coat surface). Conservation assessment – The species is only known from three localities, representing two locations.Based on the restricted area of occupancy and extent of occurrence and based on the continuing decline in area, extent and quality of habitat, the species should be considered as Endangered: EN B1a,b(iii)B2a,b(iii).